2018
DOI: 10.1002/anie.201800681
|View full text |Cite
|
Sign up to set email alerts
|

Nanoisozymes: Crystal‐Facet‐Dependent Enzyme‐Mimetic Activity of V2O5 Nanomaterials

Abstract: Nanomaterials with enzyme-like activity (nanozymes) attract significant interest owing to their applications in biomedical research. Particularly, redox nanozymes that exhibit glutathione peroxidase (GPx)-like activity play important roles in cellular signaling by controlling the hydrogen peroxide (H O ) level. Herein we report, for the first time, that the redox properties and GPx-like activity of V O nanozyme depends not only on the size and morphology, but also on the crystal facets exposed on the surface w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
96
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 210 publications
(98 citation statements)
references
References 59 publications
1
96
0
1
Order By: Relevance
“…[3,[52][53][54] It was reported that VO x nanomaterials possess excellent catalytic performance, such as peroxidase activity, which plays a key role in the bacteriostasis of VO x through the generation of * OH. [2,51,[55][56][57] This is similar with many previously reported artificial enzyme mimics, such as magnetic iron oxide, and graphene quantum dots have also been used to assist H 2 O 2 * OH for antibacterial application. [3,[58][59][60] The demonstrated antibacterial properties of VO x QDs reveal the broad application potentials in the development of antibacterial materials.…”
supporting
confidence: 71%
See 1 more Smart Citation
“…[3,[52][53][54] It was reported that VO x nanomaterials possess excellent catalytic performance, such as peroxidase activity, which plays a key role in the bacteriostasis of VO x through the generation of * OH. [2,51,[55][56][57] This is similar with many previously reported artificial enzyme mimics, such as magnetic iron oxide, and graphene quantum dots have also been used to assist H 2 O 2 * OH for antibacterial application. [3,[58][59][60] The demonstrated antibacterial properties of VO x QDs reveal the broad application potentials in the development of antibacterial materials.…”
supporting
confidence: 71%
“…It was reported that VO x nanomaterials possess excellent catalytic performance, such as peroxidase activity, which plays a key role in the bacteriostasis of VO x through the generation of . OH ,,. This is similar with many previously reported artificial enzyme mimics, such as magnetic iron oxide, and graphene quantum dots have also been used to assist H 2 O 2 .…”
Section: Methodsmentioning
confidence: 99%
“…To the best of our knowledge,t he complex protein scaffold is responsible for the high selectivity and efficiency of natural enzymes.However,nanozymes are intrinsically deficient in their fine structure and thus lack the finesse of enzyme-catalyzed reactions,t hereby resulting in unsatisfactory selectivity and activity.I na ddition, the atomic composition and structural complexity of nanomaterials endow ad iverse range of nanozyme catalytic mechanisms.F or example,m any transitionmetal-based nanozymes,such as Fe 3 O 4 , MnO 2 ,V 2 O 5 ,M oS 2 ,a nd so on, with intrinsic peroxidase,o xidase,c atalase,a nd superoxide dismutase activity,h ave been discovered. [4,[19][20][21][22][23] TheF enton or Fenton-like reactions are widely used to explain the catalytic mechanism of peroxidase mimics.T he generated COH can be used for the degradation of organic pollutants and in the treatment of cancer, as well as in biosensing applications. [24] Another catalytic mechanism of peroxidase mimics,w hich occurs in Prussian blue and its cyanometalate structural analogues,i st he electron transfer effects.…”
Section: Introductionmentioning
confidence: 99%
“…Ghosh et al extensively examined the morphology-activity correlation of orthorhombic V 2 O 5 structures of peroxidase activity [108]. Unlike Co 3 O 4 [104], they found that surface area is not a main factor in activity, but it is the accessibility of active sites on the dominant crystal faces.…”
Section: Vanadium-based Oxidesmentioning
confidence: 99%